Geoffrey Chaucer’s The Merchant’s Tale, Giovanni Boccaccio’s The Tale of the Enchanted Pear-Tree, and Sir Orfeo Viewed as Eroticized Versions of the Folktales about Supernatural Wives - Wicher, Andrzej (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Two of the tales mentioned in the title are in many ways typical of the great collections of stories (The Canterbury Tales and Il Decamerone) to which they belong. What makes them conspicuous is no doubt the intensity of the erotic desire presented as the ultimate law which justifies even the most outrageous actions. The cult of eroticism is combined there with a cult of youth, which means disaster for the protagonists, who try to combine eroticism with advanced age. And yet the stories in question have roots in a very different tradition in which overt eroticism is punished and can only reassert itself in a chastened form, its transformation being due to sacrifices made by the lover to become reunited with the object of his love. A medieval example of the latter tradition is here the Middle English romance, Sir Orfeo. All of the three narratives are conspicuously connected by the motif of the enchanted tree. The Middle Ages are associated with a tendency to moralize ancient literature, the most obvious example of which is the French anonymous work Ovide moralisé (Moralized Ovid), and its Latin version Ovidius Moralizatus by Pierre Bersuire. In the case of The Merchant’s Tale and The Tale of the Enchanted Pear-Tree, we seem to meet with the opposite process, that is with a medieval demoralization of an essentially didactic tradition. The present article deals with the problem of how this transformation could happen and the extent of the resulting un-morality. Some use has also been made of the possible biblical parallels with the tales in question.